2018
DOI: 10.22438/jeb/39/5(si)/15
|View full text |Cite
|
Sign up to set email alerts
|

Salinity effects on the development of embryos and larvae of a high-valued sea urchin, Tripneustes gratilla (Linnaeus, 1758)

Abstract: Aim: Methodology:Results: Interpretation:To investigate the standard salinity levels on the embryonic and larval development that will be helpful for the optimum growth and larval development in the seed production of for aquaculture and conservation.Gametes were collected by injecting 0.5 M KCl into coelomic cavity of the adult sea urchin, and insemination was done using 10 'dry' sperm dilution from where around 500 fertilized eggs were transferred into eight transparent plastic tubes containing 50 ml artific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Sarifudin et al (2014; [52,53] found that Diadema setosum and Salmacis sphaeroides successfully grow and develop within the salinity range from 28 to 37‰ and from 25 to 35‰, respectively. A similar optimal range of salinity (28 to 34‰) was observed in Tripneustes gratilla by Shamim Parvez et al (2018) [54], whereas Greenwood and Bennet (1981) [55], studying the effect of 45 temperature-salinity combinations on the fertilization success of the gametes of the sea urchin Parechinus angulosus, observed that temperature had the greatest effect on sperm, whereas low salinities relevantly affected the ova, but had little apparent effect on sperm. Even in Heliocidaris crassispina, low salinity and high temperature had interactive effects in reducing larval survivorship [16], whereas Metaxas (1998) [56] reported for Echinometra lucunter short-term (24 h) and long-term (over the entire developmental period) effects of salinity on larval survival and rate of development.…”
Section: Discussionsupporting
confidence: 66%
“…Sarifudin et al (2014; [52,53] found that Diadema setosum and Salmacis sphaeroides successfully grow and develop within the salinity range from 28 to 37‰ and from 25 to 35‰, respectively. A similar optimal range of salinity (28 to 34‰) was observed in Tripneustes gratilla by Shamim Parvez et al (2018) [54], whereas Greenwood and Bennet (1981) [55], studying the effect of 45 temperature-salinity combinations on the fertilization success of the gametes of the sea urchin Parechinus angulosus, observed that temperature had the greatest effect on sperm, whereas low salinities relevantly affected the ova, but had little apparent effect on sperm. Even in Heliocidaris crassispina, low salinity and high temperature had interactive effects in reducing larval survivorship [16], whereas Metaxas (1998) [56] reported for Echinometra lucunter short-term (24 h) and long-term (over the entire developmental period) effects of salinity on larval survival and rate of development.…”
Section: Discussionsupporting
confidence: 66%
“…A decrease in salinity depressed the fertilization ability of the collector sea urchin, especially in combination with the lowest (24°C) and the highest (36°C) temperatures, while a salinity of 23‰ inhibited it. However, fertilization was still possible in this minimal salinity (i.e., 23‰) that matched with the lower limit of resistance of adult individuals of the collector sea urchin [40,41]. A similar phenomenon was also recorded in other echinoderms, such as cucumaria sea cucumber (Eupentacta fraudatrix), and sea stars (Asterias amurensis and Asterina pecinifera), although fertilization in these species was still observed at the minimum salinity levels (20‰ and 18‰, respectively), which were lower than in T. gratilla [42,43,44,45].…”
Section: Discussionmentioning
confidence: 93%
“…Large-scale T. gratilla fisheries, responsible for catching hundreds of tons of urchins, have been reported in the Philippines, Fiji and Japan [3]. Urchin gonads, known as roe, are a luxury delicacy that can command astronomical prices, over US$1000/kg, making them one of the most expensive seafood products in the world [11,58]. With the ever-increasing demand for roe and the general decline in sea urchin fisheries, an opportunity for aquaculture and stock enhancement is bourgeoning [40,65].…”
Section: Discussionmentioning
confidence: 99%